Towards Healthy Aging with Physical Activity and Nutrition - Listya Tresnanti Mirtha; Angela Tulaar; I Dewa Putu Pramantara (Amerta Nutrition, 2020)
Background. Indonesia has become the country with the highest elderly population in Southeast Asia which around 27 million people within 2020. Demographic bonus, where the productive age is higher than the non-productive age, should be optimized so that it becomes an opportunity to decrease the dependency ratio of the elderly over 65 years. However, increasing life expectancy has other implications which as the increase in health problems associated with the aging process, including the emergence of degenerative diseases. The concept of healthy aging formed due to the increase of public awareness to live within quality life and maintaining a healthy lifestyle through physical activity and good nutrition. Healthy aging is the process of developing and maintaining the functional ability that enables wellbeing in older age. Lifestyle improvement from the early stage will have a better effect on a person's lifelong health. Unfortunately, it is not widely known by the public, so awareness is not yet evident and benefits cannot be obtained optimally.Objectives. Healthy aging is the process of developing and maintaining the functional ability that enables wellbeing in older age. The aim of this review is to raise awareness among the adult age group about the important role of physical activity and nutrition in achieving a healthy aging condition.Discussion. American College of Sports Medicine (ACSM) and Centers for Disease Control and Prevention (CDC) recommend adults aged 18–65 year to participate in moderate-intensity aerobic physical activity for a minimum of 30 minutes on five days per week, or vigorous-intensity aerobic activity for a minimum of 20 minutes on three days per week. Moreover, recent WHO (2020) guideline towards physical activity and sedentary behavior recommend all adults to have moderate-intensity for 150 – 300 min or vigorous-intensity for 75 – 150 min per week. But this recommendation has not been able to reduce physical inactivity number in Indonesian society, especially adult and senior adult. There are some nutrition elements related to mobility health, mainly are protein, vitamin D, calcium, antioxidant and omega-3, and many studies report that Indonesian adults suffer deficiencies on these nutrition elements and cause health problems related to mobility. Health interventions should involved many stakeholders, e.g government, private sectors, NGO, mass media, and many more.Conclusions: The concept of healthy aging and interventions related to this need to be recognized and implemented as early as possible to get optimal results, and preferably starting from adulthood. Health interventions carried out must be holistic and synergize between physical activity, nutrition, mental health and other factors that play a role. A community-based approach is the easiest and fastest way to change mindsets and behavior patterns, and can be implemented in the work environment or other communities.